2017
DOI: 10.3390/rs9040327
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Validation of SMAP Soil Moisture Products over Cold and Arid Regions in Northwestern China Using Distributed Ground Observation Data

Abstract: Abstract:The Soil Moisture Active Passive (SMAP) mission was designed to provide global mapping of soil moisture (SM) on nested 3, 9, and 36 km earth grids measured by L-band passive and active microwave sensors. The validation of SMAP SM products is crucial for the application of the products and improvement of the retrieval algorithm. Since the SMAP SM products were released, much effort has been invested in the evaluation of the SMAP radiometer SM product (SMAP_P). However, there has been little validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…The thiessen polygon method adopted for SMAP SM validation [41] was used to upscale point-based field SM to pixel-based SM, to reduce the uncertainty of validation caused by the spatial mismatch between ground observations and satellite results. The thiessen polygon method was carried out based on a Matlab code by combining spatial location of SM observing points and the boundary of satellite footprint.…”
Section: E Error Metricsmentioning
confidence: 99%
“…The thiessen polygon method adopted for SMAP SM validation [41] was used to upscale point-based field SM to pixel-based SM, to reduce the uncertainty of validation caused by the spatial mismatch between ground observations and satellite results. The thiessen polygon method was carried out based on a Matlab code by combining spatial location of SM observing points and the boundary of satellite footprint.…”
Section: E Error Metricsmentioning
confidence: 99%
“…These in situ networks are located in different climates and environments, which largely compensate for the lack of SM observations in typical polar climates. Based on these in situ measurements, satellite-derived SM-validation studies have been conducted over the QTP and its surrounding areas [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [24] evaluated the SMAP and SMOS SM products by using observations from the Naqu and Pali networks over the QTP, and the results showed that SMAP adequately captured the temporal variations and amplitudes of in situ SM, while SMOS failed to capture temporal variations in SM, especially in an in situ network in a semiarid area of the southern QTP. Ma et al [25] conducted a multiscale validation of SMAP SM products in the Heihe River basin and found that the vegetation effect may have been a major factor that caused slightly unsatisfactory performance, but SMAP maintained consistent spatial-temporal variations with the in situ measurements and typical precipitation events. Recently, Zheng et al [26] evaluated SMAP products in the Maqu and Ngari networks of the QTP and assessed the effect of vegetation opacity and other factors on SM retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…The median value of RMSE decrease from GPM to SMP is more than 20% for LAI ranging from 1 to 2, and this improvement becomes less effective as LAI increases. Although L-band measurements used in SMAP are less sensitive to vegetation than C-band measurements due to the low noise produced with SMAP [66], the SMAP soil moisture is still substantially biased over vegetated areas [67,68]. The lower quality of SMAP soil moisture over vegetated areas may lead to less improvement from GPM estimates to SM corrected precipitation.…”
Section: Discussionmentioning
confidence: 99%